Use of cone beam CT in children and young people in three United Kingdom dental hospitals. Issue 5 (31st October 2013) - Hidalgo‐Rivas, Jose Alejandro; Theodorakou, Chrysoula; Carmichael, Fiona; Murray, Brenda; Payne, Martin; Horner, Keith
<x xml:space="preserve">Abstract</x> Background There is limited evidence about the use of cone‐beam computed tomography (CBCT) in paediatric dentistry. Appropriate use of CBCT is particularly important because of greater radiation risks in this age group. Aim To survey the use of CBCT in children and young people in three Dental Hospitals in the United Kingdom (UK), with special attention paid to aspects of justification and optimisation. Design Retrospective analysis of patient records over a 24‐month period, looking at CBCT examinations performed on subjects under 18 years of age. Clinical indications, region of interest, scan field of view (FoV), incidental findings and exposure factors used were recorded. Results There were 294 CBCT examinations performed in this age group, representing 13.7% of all scanned patients. CBCT was used more frequently in the >13 year age group. The most common use was for localisation of unerupted teeth in the anterior maxilla and the detection of root resorption. Optimisation of X‐ray exposures did not appear to be consistent. Conclusions When planning a CBCT service for children and young people, a limited FoV machine would be the appropriate choice for the majority of clinical requirements. It would facilitate clinical evaluation of scans, would limit the number of incidental findings and contribute to optimisation of radiation doses.